2020
DOI: 10.26686/wgtn.12469334.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale

Abstract: © 2019 John Wiley & Sons Ltd Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large-scale patterns of species richn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
1
12
1
Order By: Relevance
“…To characterize human disturbance of natural systems, we used the terrestrial Human Footprint for 2009 (Venter et al, 2018). This source of data has often been used to analyse the influence of human activities on biodiversity (Garnett et al, 2018; Sebastián‐González et al, 2019). We z ‐scored all variables to facilitate the comparison across models (Schielzeth, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…To characterize human disturbance of natural systems, we used the terrestrial Human Footprint for 2009 (Venter et al, 2018). This source of data has often been used to analyse the influence of human activities on biodiversity (Garnett et al, 2018; Sebastián‐González et al, 2019). We z ‐scored all variables to facilitate the comparison across models (Schielzeth, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Scavenging, where organisms from microbes to vertebrates compete to consume ephemeral carrion, is an important ecological process (Sebastián‐González et al, 2019; Wilmers, Stahler, Crabtree, Smith, & Getz, 2003). Scavengers provide functions in ecosystems and to humanity by removing decaying carrion and potentially harmful pathogens, as well as stabilizing food webs (Ćirović, Penezić, & Krofel, 2016; Sebastián‐González et al, 2020; Wilson & Wolkovich, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Global change (i.e., changing climate and increasing human impact) may alter important ecological interactions (Sebastián‐González et al, 2019). It is suggested that vertebrate scavenger species richness is strongly negatively affected by humans (Sebastián‐González et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Global change (i.e., changing climate and increasing human impact) may alter important ecological interactions (Sebastián‐González et al, 2019). It is suggested that vertebrate scavenger species richness is strongly negatively affected by humans (Sebastián‐González et al, 2019). In some environmental settings, higher human population density can reduce scavenger richness and diversity due to habitat fragmentation and fatality from conflict or road deaths (Crooks et al, 2011; Hagen et al, 2012; McKinney, 2008; Planillo et al, 2018; Sebastián‐González et al, 2019; Treves & Karanth, 2003).…”
Section: Introductionmentioning
confidence: 99%